Synthesis of Activated Carbon/Magnetite Nanocomposite Modified with Povidone for Adsorption Applications of Heavy Metal Ions - Muhammad Zainullah; Muhammad Safwan Aziz; Nurul Hidayat; Lya Rizka Herawati; Ahmad Taufiq (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
This study reports on activated carbon/magnetite nanocomposite modified with povidone for the adsorption applications of heavy metal (lead) ions. The synthesis routes used in this study were coprecipitation, activated carbon activation, and ex-situ methods. The data analysis results showed that the activated carbon/magnetite nanocomposite modified with povidone had a crystallite size of 9.45 nm with a single-phase inverse cubic spinel structure. The activated carbon/magnetite nanocomposite modified with povidone showed successful synthesis with the appearance of octahedral and tetrahedral Fe–O lattice vibrations (440 and 550 cm–1), O–H (3200–3395 cm–1), C=O (1655 cm–1), and C–N (1182 cm–1) functional groups. Furthermore, the activated carbon/magnetite nanocomposite modified with povidone exhibited a chunky and spherical morphology, with a particle size of 39.91 nm. The nanocomposite had a large specific surface area and pore volume, namely 129.237 m2/g and 0.198 cm3/g, respectively, thus providing many active sites for adsorption. Interestingly, the nanocomposite was superparamagnetic, facilitating its separation from the solution after adsorption. The adsorption efficiency of this nanocomposite was 71.01% with an adsorption capacity of 29.6415 mg/g in 180 minutes at a volume of heavy metal solution of 25 mL with a theoretical concentration of 100 ppm, adsorbent dose of 0.05 g, pH 5, and room temperature, and followed with pseudo-second order adsorption kinetics model. The resulting removal efficiency is better than magnetite/povidone, which has a removal efficiency of 70%.